Center Learning Innovation: Implementing The Steamly Plus Approach to Develop Creativity and Skills in Early Childhood - Reksadini, Marda Ulya; Zaroh, Ulfi Choirul; Noviana, Fina Ayu; Komalasari, Suci (THUFULA, 2025)
This research aims to analyze the effectiveness and impact of implementing the center learning model with the Steamly Plus approach on developing basic skills and children’s learning interests. The STEAMLY Plus approach emphasizes creativity, critical skills, and problem solving which are very important for the cognitive and emotional development of early childhood. This learning is the foundation for developing 21st century skills. The method used is classroom action research conducted by teachers in their classes through self-reflection carried out in a planned, systematic, and repeated manner in an action cycle. The study results showed that implementing STEAMLY Plus in the Center Learning Model at PAUD Islam Makarima Sukoharjo was 70% effective in improving children’s holistic skills. The impact of implementing the STEAMLY Plus approach on improving children’s holistic skills includes balanced development in various aspects. Cognitively, children experience increased abilities through activities integrating science, technology, engineering, art, and mathematics. In terms of social and emotional, children learn to interact and collaborate. Interest in learning is seen directly in learning activities, such as actively participating in experiments, discussions, or projects. Children with concrete learning interests tend to be more enthusiastic, open to new experiences, and willing to repeat enjoyable activities.